2015
DOI: 10.3390/md13053046
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Restenotic Roles of Dihydroaustrasulfone Alcohol Involved in Inhibiting PDGF-BB-Stimulated Proliferation and Migration of Vascular Smooth Muscle Cells

Abstract: Dihydroaustrasulfone alcohol (DA), an active compound firstly isolated from marine corals, has been reported to reveal anti-cancer and anti-inflammation activities. These reported activities of DA raised a possible application in anti-restenosis. Abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) and the stimulation of platelet-derived growth factor (PDGF)-BB play major pathological processes involved in the development of restenosis. Experimental results showed that DA markedly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…In patients with other inflammatory diseases, there is evidence of cross-talk between ERK1/2 MAPK with STAT1 signaling, which results in radical oxygen generation and histone modification. [31][32][33] In addition, ERK1/2 MAPK signaling plays an important role in the regulation of cell proliferation, migration, differentiation, and angiogenesis, suggesting a role for PRMT1 in these events. 34,35 In this study we observed that inhibition of ERK1/2 MAPK suppressed STAT1 phosphorylation, which is consistent with the findings of others.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with other inflammatory diseases, there is evidence of cross-talk between ERK1/2 MAPK with STAT1 signaling, which results in radical oxygen generation and histone modification. [31][32][33] In addition, ERK1/2 MAPK signaling plays an important role in the regulation of cell proliferation, migration, differentiation, and angiogenesis, suggesting a role for PRMT1 in these events. 34,35 In this study we observed that inhibition of ERK1/2 MAPK suppressed STAT1 phosphorylation, which is consistent with the findings of others.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, secretory smooth muscle cells synthesize and secrete high levels of various cytokines and adhesion molecules, which promote the early occurrence of local inflammatory reactions of the damaged vessel and form an extremely complicated inflammation network control system via the sequential activation of multiple overlapping intracellular signal pathways. Moreover, this process causes the chemotaxis of inflammatory cells and inflammatory cell aggregation and adhesion, aggravates inflammatory reactions, induces local lesion of the vessel, and promotes postintervention restenosis [34,35]. Therefore, further research on inflammation-activated smooth muscle cells is important for the prevention and treatment of restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…VSMCs undergo a rapid and reversible change from a quiescent contractile phenotype to a proliferative synthetic phenotype, induced by increased degradation of extracellular matrix proteins, such as gelatin and collagen (Chaabane et al, ). Such decomposition of the extracellular matrix facilitates the induction of VSMC migration (Li et al, ). Phosphorylation of focal adhesion kinase (FAK) has a significant effect on VSMC migration by affecting cytoskeletal remodelling.…”
Section: Introductionmentioning
confidence: 99%